MULTICULTURAL FIQH: THE INDIGENIZATION OF ISLAM, MULTICULTURALISM, AND MAQĀṢID AL-SHARĪʿAH (ASSESSING ABDURRAHMAN WAHID’S INTELLECTUAL CONTRIBUTION) - Zuhri Humaidi (Jurnal Dinamika Ekonomi Syariah, 2025)
The Indigenization of Islam (Pribumisasi Islam) is one of the central ideas in Abdurrahman Wahid’s thought and has generated extensive intellectual discussion. It is intended to create space for diverse interpretations and manifestations of Islamic teachings within different cultural settings. Nevertheless, the idea was formulated amid the New Order’s discourses of modernization, developmentalism, and the commodification of culture. This article therefore re-examines Wahid’s discourse through the perspectives of multiculturalism and Maqāṣid al-Sharīʿah (the higher objectives of Islamic law). Using conceptual and philosophical-legal approaches, the study produces three main findings. First, within Wahid’s framework of indigenization, fiqh occupies the central problematic because it can become a key to either the advancement or the decline of the Muslim community. However, indigenization is primarily directed toward reconciling tensions between religion and culture and is not yet fully developed as resistance to dominant constructions of religion, locality, and culture. Second, Multicultural Fiqh extends the concept of indigenization by offering a model of fiqh practice that protects cultural existence while also challenging hegemonic relations of power in religious and cultural life in Indonesia. Third, Multicultural Fiqh is grounded in the values of Maqāṣid al-Sharīʿah and the cosmopolitan character of Islamic jurisprudence, expressed through a critical openness to accommodating, preserving, and evaluating tradition